Untargeted Metabolomics for Autism Spectrum Disorders: Current Status and Future Directions - Glinton, Kevin E.; Elsea, Sarah H. (Frontiers in Psychiatry, 2019)
Autism spectrum disorders (ASD’s) are a group of neurodevelopment disorders characterized by childhood onset deficits in social communication and interaction. Though the exact etiology of most cases of ASD’s are unknown, a portion have been proposed to be associated with various metabolic abnormalities including mitochondrial dysfunction, disorders of cholesterol metabolism and folate abnormalities. Targeted biochemical testing like plasma amino acid and acylcarnitine profiles have demonstrated limited utility in helping to diagnosis and manage such patients. Untargeted metabolomics has emerged, however, as a promising tool in screening for underlying biochemical abnormalities, managing treatment, and as a means of investigating possible novel biomarkers for the disorder. Here, we review the principles and methodology behind untargeted metabolomics, recent pilot studies utilizing this technology, ,and areas in which it may be integrated into the care of children with this disorder in the future